Intelligent Class Program Management (CI) Al Azhar Syifa Budi a Legend In Bekasi - Qathrunnada Qathrunnada; Noviyanto Noviyanto (PT. Publikasiku Academic Solution, 2022)
Background: Constitution Number 20 Years 2003 about The National Education System in article 5 paragraph (4) states that :